2011
DOI: 10.2511/027494811800824507
|View full text |Cite
|
Sign up to set email alerts
|

What is Literacy? The Power of a Definition

Abstract: People with extensive needs for support represent the last group of people routinely denied opportunities for literacy instruction. One of the major reasons for this lack of opportunity can be related to limited definitions of what constitutes literacy as a whole and reading and writing in particular. This article will explore the way in which definitions of literacy impact literacy opportunities for individuals with extensive needs for supports. We propose a set of core definitional principles and make explic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 26 publications
1
74
0
6
Order By: Relevance
“…Scribner first imagines literacy as a means for survival, in its pragmatic form. Keefe and Copeland (2011) and UNESCO (2008) echo that literacy is a human right and necessary for survival in contemporary society. Therefore, all persons must be able to navigate the world around them, read and understand their rights (Stromquist, 2009).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Scribner first imagines literacy as a means for survival, in its pragmatic form. Keefe and Copeland (2011) and UNESCO (2008) echo that literacy is a human right and necessary for survival in contemporary society. Therefore, all persons must be able to navigate the world around them, read and understand their rights (Stromquist, 2009).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…While literacy is a universal right, necessary to both daily living and social agency, it is not enough to believe that all persons should be literate; educators must understand literacy as a social and interactive experience. Literacy is a social enterprise that is culturally transmitted, requires interaction, and it occurs in social contexts (Keefe & Copeland, 2011;Kliewer, 1998;Scribner, 1984). Kliewer established the argument that if educators expand how they define what it means to be literate, students with disabilities and struggling readers could participate in the construction of meaning alongside their grade-level peers, and therefore realize literate capacities.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Though the term disingenuously appears simple to everyone but it has proved to be both complex and dynamic, continuing to be interpreted and defined in a multiplicity of ways. What people think of what it means to be literate or otherwise are influenced by academic research, institutional agendas, national context, cultural values and personal experiences (Education for All Global Monitoring Report, 2006; Keefe and Copeland, 2011). Traditionally, literacy has been closely associated with the ability to read and write.…”
Section: Literacy and Its Importancementioning
confidence: 99%
“…According to United Nations Educational, Scientific and Cultural Organization (UNES- CO, 2006) as cited in Adelore and Itasanmi (2016), there are different dimensions to literacy as it often emphasizes the ability to understand and communicate through a written text, however, there is no universally accepted definition that captures all its facets. UNESCO (2008) in Keefe and Copeland (2011), observed that a person is literate who can with understanding both read and write a short simple statement on his/her daily life. It went further to state that a person is functionally literate when he/she can engage in all those activities in which literacy is required for effective functioning of his/her group and community and also for enabling him/ her to continue to use reading, writing and calculation for his/her own and the community's development.…”
Section: Literacy and Its Importancementioning
confidence: 99%
“…Okuryazarlık, bir bireyin günlük yaşamdaki kısa, basit ifadeleri anlayarak okuma ve yazma yeteneğini ifade eder (Keefe ve Copeland, 2011). Okuryazarlık, yazılı veya görsel semboller kullanarak bireyler arasındaki iletişimi sağlayacak düzeyde okuma ve yazma yeteneğidir.…”
Section: Introductionunclassified